TEACHER’S PERCEPTION TOWARDS THE IMPLEMENTATION OF THE TEACHER’S COMPETENCY TEST AT SMA N 3 BANDAR LAMPUNG 2012/2013 - nevita safutri warganegara; Berchah Pitoewas; Hermi Yanzi (FKIP Unila, 2012)
This research was intended to analysis and to explain about teacher’s perception towards the implementation of the teacher’s competency test (TCT) at SMA 3 Bandar Lampung 2012/2013 that used by education department in Bandar Lampung 2012. In this research, the researcher used descriptive method. The population of this research was 50 teachers of SMA 3 Bandar Lampung. The data collecting technique in this research were questionnaires, analysis technique and percentage. Based on the calculation of data analysis, the result showed that teacher’s perception towards of the implementation of TCT at SMA 3 Bandar Lampung in teacher’s experience aspect were 29 teachers (58%) included to average category. Teacher’s perception towards the implementation of teacher’s competency test in teacher’s income aspect were 26 teachers (52%) included to average category. Teacher’s perception towards the implementation of teacher’s competency tets (TCT) in teacher’s knowledgment aspect were 23 teachers (46%) included to good category. Thus, it was concluded that the implementation of TCT which have done for mapping competencies and as a basis for continuing professional development activities well, but still need to be aware that TCT has not been running smoothly and there were still some of these constraints, the editors about using the word convoluted and difficult to understand and a lot of the content was too high level, the question of social competence there was discrepancy between the question and the answers and the lack of socialization that was done by the education department and guarantee agency lampung province education and the lack of coordination and responsibility of the implementing organization and committees in the implementation of TCT 2012/2013.Keywords: Teacher’s Competency Test.